2019
DOI: 10.1101/780635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spinal signaling of C-fiber mediated pleasant touch in humans

Abstract: 1 C-tactile afferents form a distinct channel that encodes pleasant tactile stimulation. Prevailing 2 views indicate they project, as with other unmyelinated afferents, in lamina I-spinothalamic 3 pathways. However, we found that spinothalamic ablation in humans, whilst profoundly im-4 pairing pain, temperature and itch, had no effect on pleasant touch perception. Only discrimi-5 native touch deficits were seen. These findings preclude privileged C-tactile-lamina I-spinotha-6 lamic projections and imply integr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Although our clinical groups showed reduced perceived pleasantness for CT-optimal stimulation in comparison to healthy volunteers, this finding applied for non-CT-optimal touch too. More broadly, while microneurography and psychophysical investigations have indicated that C-tactile afferents have peak firing rates that positively correlate with the perceived touch pleasantness of gentle touch (Löken et al, 2009), a recent study showed that spinothalamic ablation in humans had no effect on pleasant touch perception, suggesting a more integrated hedonic and discriminative spinal processing from the body (Marshall et al, 2019). Thus, future studies in AN need to explore further tactile and interoceptive modalities in order to draw firm conclusions about the mechanisms that cause tactile anhedonia in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our clinical groups showed reduced perceived pleasantness for CT-optimal stimulation in comparison to healthy volunteers, this finding applied for non-CT-optimal touch too. More broadly, while microneurography and psychophysical investigations have indicated that C-tactile afferents have peak firing rates that positively correlate with the perceived touch pleasantness of gentle touch (Löken et al, 2009), a recent study showed that spinothalamic ablation in humans had no effect on pleasant touch perception, suggesting a more integrated hedonic and discriminative spinal processing from the body (Marshall et al, 2019). Thus, future studies in AN need to explore further tactile and interoceptive modalities in order to draw firm conclusions about the mechanisms that cause tactile anhedonia in this population.…”
Section: Discussionmentioning
confidence: 99%
“…heart rate), others such as noxious or gentle skin stimulation tend to also convey hedonic and motivational signals. Of interest here, 'affective touch', hereafter referring to a specialised tactile modality of gentle, stroking touch, thought to be (at least partly, see Marshall et al, 2019) mediated peripherally by unmyelinated, slowconducting C-tactile (CT) afferents (Löken et al, 2009) and to be centrally processed by an interoceptive pathway converging at the insular cortex (Morrison, 2016;Kirsch et al, 2020), has been associated with subjective sensations of skin pleasure (Löken et al, 2009) and related behavioural measures (Pawling et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike myelinated afferents, C-tactiles are tuned to respond to slowly moving stimuli ( Löken et al , 2009 ), and their preferred speeds are similar to the optimal speed for TDD ( Dreyer et al , 1978 ; Essick and Whitsel, 1985 ). It thus seems possible that the C-tactile afferent insular pathway may play a role in TDD processing in addition to its role in affective touch ( Marshall et al , 2019 ). However, the task specificity of insular involvement with the TDD task is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Current views of the somatosensory representation of valenced information from the sensory surface are mostly based on examination of pain alone. While considerable research supports the neural bases of pain-coding in the periphery (McGlone and Reilly, 2010;Nagi et al, 2019), recent evidence indicates parallel C-tactile (CT) sensory fibers for caress or pleasant touch (Loken et al, 2009;Marshall et al, 2019). In this system, mechanoreceptors are found only in hairy skin and not on the glabrous (i.e., hairless) skin of the palms, where previous research had focused (McGlone and Reilly, 2010;McGlone et al, 2014;Marshall et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…Rather, it projects to an anterior region of S1 (insula-adjacent area 3a; Vierck et al, 2013; Whitsel et al, 2009), with additional direct projections to the insula, anterior cingulate cortex (ACC), and PFC (Baumgartner et al, 2006; Qiu et al, 2006). Similarly, recently identified pathways – C-tactile (CT) fibers – have been shown to carry information about caress or pleasant touch (Loken et al, 2009; Marshall et al, 2019). These fibers originate from mechanoreceptors located in hairy skin rather than the glabrous (i.e., hairless) skin of the palms, where previous research has focused (Marshall et al, 2019; McGlone & Reilly, 2010; McGlone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%